2015
DOI: 10.1161/jaha.115.002128
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine Acutely Suppresses Local Cardiac Production of Inflammatory Cytokines in Patients With an Acute Coronary Syndrome

Abstract: BackgroundInterleukin (IL)-1β, IL-18, and downstream IL-6 are key inflammatory cytokines in the pathogenesis of coronary artery disease. Colchicine is believed to block the NLRP3 inflammasome, a cytosolic complex responsible for the production of IL-1β and IL-18. In vivo effects of colchicine on cardiac cytokine release have not been previously studied. This study aimed to (1) assess the local cardiac production of inflammatory cytokines in patients with acute coronary syndromes (ACS), stable coronary artery d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
179
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 242 publications
(192 citation statements)
references
References 50 publications
7
179
0
6
Order By: Relevance
“…A corresponding decrease in pro-IL-1β mRNA was not observed, thus suggesting colchicine does not alter gene transcription of IL-1β and reduction in protein levels is due to a post-translational cleavage. Such findings are at least partially consistent with our previous study, where coronary levels of IL-1β and IL-18 were significantly reduced by colchicine therapy (15). In this study, the less marked effect on IL-18 secretion can be explained by the fact that IL-18 might also be secreted by non-monocyte resident cells in the vessel wall or other circulating leucocytes, on which colchicine could also inhibit, in contrast, the reduction in IL-1 secretion into the coronary circulation can be attributed, at least partly, to the action of colchicine on monocyte activation.…”
Section: Increased Production Of Inflammasome-related Cytokines From supporting
confidence: 93%
See 2 more Smart Citations
“…A corresponding decrease in pro-IL-1β mRNA was not observed, thus suggesting colchicine does not alter gene transcription of IL-1β and reduction in protein levels is due to a post-translational cleavage. Such findings are at least partially consistent with our previous study, where coronary levels of IL-1β and IL-18 were significantly reduced by colchicine therapy (15). In this study, the less marked effect on IL-18 secretion can be explained by the fact that IL-18 might also be secreted by non-monocyte resident cells in the vessel wall or other circulating leucocytes, on which colchicine could also inhibit, in contrast, the reduction in IL-1 secretion into the coronary circulation can be attributed, at least partly, to the action of colchicine on monocyte activation.…”
Section: Increased Production Of Inflammasome-related Cytokines From supporting
confidence: 93%
“…In this environment, ATP (the second stimulus required for complete inflammasome activation) might be secreted by inflammatory cells or aggregated platelets (26), alternatively it might be released from activated monocytes, leading to autocrine activation of the P2X7 receptor (27). We have previously shown release of inflammasome-related cytokines in the coronary circulation in ACS patients, supporting the concept of complete inflammasome activation in vivo (15).…”
Section: Increased Production Of Inflammasome-related Cytokines From mentioning
confidence: 63%
See 1 more Smart Citation
“…12, 13 In this study, colchicine tended to reduce the serum level of hs-cTnI at 24 h after MI, but this was not significantly different compared with the vehicle group. A previous study using a canine ischemia and reperfusion injury model concluded no myocardial protective effect of colchicine was observed, despite a reduction in neutrophil reactive oxygen species and accumulation in the myocardium.…”
Section: Discussionmentioning
confidence: 53%
“…11 Colchicine was reported to reduce inflammatory cytokines (including IL-1β and IL-18) and infarction size in MI. 12, 13 However, the sustained benefit of short-term colchicine treatment on survival, cardiac function, and ventricular remodeling after MI is unknown.…”
mentioning
confidence: 99%